MANAJEMEN KONFLIK DALAM LEMBAGA PENDIDIKAN MUHAMMADIYAH KABUPATEN LAMPUNG TIMUR - Sumaryati, Sumaryati (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to analyze identifying causes of conflict, analyzing the impact of the conflict, conflict resolution, and the conflict management strategy in Muhammadiyah’s educational institutions in East Lampung. This study uses a qualitative approach. Data collection is done by using in-depth interviews, observations, and documentation. The results of the study show that there are differences of opinion, job dependence, differences in status and roles, e.g. communication, division of tasks, delay in honorarium, financial management, misunderstanding, being too sensitive. The impact of the conflict caused by being functional, such as being cooperative, prioritizing the interests of the institution, raising awareness of organization, finding the best solution, getting wiser in making decisions. Disfunctional nature such as uncomfortable working atmosphere, decreased performance, lack of enthusiasm, coming late to go home early, work atmosphere becomes tense, work hampered and delay in achieving targets. Conflict resolution is carried out by the principal by deliberation, advising, strengthening ties, compromise, accepting joint decisions based on spiritual values guided by the Qur'an and Hadith and heeding the Memorandum and Articles of Association (ADART) of the Dikdasmen Council. (4) The conflict management strategy used is collaboration, compromise and accommodation.